2010
DOI: 10.1103/physrevb.81.184302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum state of hydrogen inLaNi5

Abstract: The quantum state of the hydrogen atom that is trapped at the most stable octahedral interstitial site in the LaNi 5 crystal is determined. A three-dimensional potential-energy surface for the hydrogen atom around the 3f site is obtained by applying first-principles electronic-structure calculations. The time-independent Schrödinger equation for the hydrogen atom under the potential obtained is solved. The hydrogen wave function distributes over the neighboring sites, 6i-3f-6i, that have been proposed by vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…2(a), the potential energy surface has a potential minimum point at the classical hydrogen position, while the potential energy surface at the 6i site for the solid solution phase has two minimum potential points. 3,4 In this case, the potential energy surface has a step structure in the Z direction as explained latter (see Fig. 3), and its step height is 0.25 eV, which is comparable to the zero point energy of the hydrogen atom.…”
Section: B Potential Energy Surfacementioning
confidence: 52%
See 2 more Smart Citations
“…2(a), the potential energy surface has a potential minimum point at the classical hydrogen position, while the potential energy surface at the 6i site for the solid solution phase has two minimum potential points. 3,4 In this case, the potential energy surface has a step structure in the Z direction as explained latter (see Fig. 3), and its step height is 0.25 eV, which is comparable to the zero point energy of the hydrogen atom.…”
Section: B Potential Energy Surfacementioning
confidence: 52%
“…These are powerful tools for exploring the quantum effects of light nuclei on neutron scatterings from dilute hydrogen in a solid solution of LaNi 5 H 0:5 . 3 We also showed that some zero point vibrational effects are present at all hydrogen sites in the solid solution phase of LaNi 5 H. 4 Some sites are combined into one site due to the zero point vibration. In this study, we reveal the hydrogenatom quantum effects in the hydride, and we clarify their role.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The hydrogen nuclear wavefunctions were calculated by solving the Schrödinger equation under the theoretical adiabatic potential [10][11][12][13][14]. Sugimoto and Fukai [11] calculated hydrogen nuclear wave functions using an empirical interatomic potential.…”
Section: Introductionmentioning
confidence: 99%
“…The potential in the reciprocal space was obtained from the Fourier transformation of the total energies of the crystals whose unit cells contained a hydrogen atom at several positions on the high-symmetry paths. Kaneko et al [14] calculated the hydrogen nuclear wavefunctions and the INS peak energies for a more complicated material, a hydrogen primary solid solution of LaNi 5 , and calculated the adiabatic potential through first-principles band calculations of a model structure of the solid solution with the hydrogen atom placed on mesh grids in a box centered at a hydrogen interstitial site. However, more than one primary peak in each experimental INS collected with the momentum transfer vector perpendicular and parallel to the c-axis of the hexagonal crystal [7] was unassigned by the calculated hydrogen nuclear states of the primary hydrogen interstitial site.…”
Section: Introductionmentioning
confidence: 99%